Case report: A novel homozygous histidine triad nucleotide-binding protein 1 mutation featuring distal hereditary motor-predominant neuropathy with rimmed vacuoles - Jiang, Nan; Vazquez Do Campo, Rocio; Kazamel, Mohamed (Frontiers in Neurology, 2023)
Introduction Recessive mutations in the gene encoding the histidine triad nucleotide-binding protein 1 (HINT1) are associated with axonal motor-predominant Charcot–Marie–Tooth (CMT) disease with neuromyotonia. A total of 24 HINT1 gene mutations have been reported so far. Some of these cases had mild to moderate elevations of creatinine kinase with no earlier reports of muscle biopsy findings in these cases. In this study, we describe a patient with axonal motor-predominant neuropathy and myopathy with rimmed vacuoles, likely due to a novel HINT1 gene mutation. Case report A 35-year-old African American man presented with insidious onset and progressive symmetric distal leg weakness followed by hand muscle atrophy and weakness since the age of 25. He had no muscle cramps or sensory complaints. His 38-year-old brother developed similar symptoms beginning in his early 30 s. On neurologic examination, the patient had distal weakness and atrophy in all limbs, claw hands, pes cavus, absent Achilles reflexes, and normal sensory examination. Electrodiagnostic studies revealed absent/reduced compound motor action potential amplitudes distally with normal sensory responses with no neuromyotonia. His sural nerve biopsy showed a chronic non-specific axonal neuropathy, and a biopsy of the tibialis anterior muscle demonstrated myopathic features and several muscle fibers harboring rimmed vacuoles without inflammation in addition to chronic denervation changes. A homozygous variant, p.I63N (c.188T > A), in the HINT1 gene was found in both brothers. Conclusion We describe a novel, likely pathogenic, HINT1 pI63N (c.188T > A) homozygous variant associated with hereditary axonal motor-predominant neuropathy without neuromyotonia in two African American brothers. The presence of rimmed vacuoles on muscle biopsy raises the possibility that mutations in the HINT1 gene may also cause myopathy.